Impact of Plant Growth Promoting Bacteria on Salicornia ramosissima Ecophysiology and Heavy Metal Phytoremediation Capacity in Estuarine Soils - Mesa-Marín, Jennifer; Pérez-Romero, Jesús A.; Redondo-Gómez, Susana; Pajuelo, Eloísa; Rodríguez-Llorente, Ignacio D.; Mateos-Naranjo, Enrique (Frontiers in Microbiology, 2020)
Salicornia ramosissima is a C3 halophyte that grows naturally in South Western Spain salt marshes, under soil salinity and heavy metal pollution (mostly Cu, Zn, As, and Pb) caused by both natural and anthropogenic pressure. However, very few works have reported the phytoremediation potential of S. ramosissima. In this work, we studied a microbe-assisted phytoremediation strategy under greenhouse conditions. We inoculated plant growth promoting (PGP) and heavy metal resistant bacteria in pots with S. ramosissima and natural non-polluted and polluted sediments collected from Spanish estuaries. Then, we analyzed plant ecophysiological and metal phytoaccumulation response. Our data suggested that inoculation in polluted sediments improved S. ramosissima plant growth in terms of relative growth rate (RGR) (32%) and number of new branches (61%). S. ramosissima photosynthetic fitness was affected by heavy metal presence in soil, but bacteria inoculation improved the photochemical apparatus integrity and functionality, as reflected by increments in net photosynthetic rate (21%), functionality of PSII (Fm and Fv/Fm) and electron transport rate, according to OJIP derived parameters. Beneficial effect of bacteria in polluted sediments was also observed by augmentation of intrinsic water use efficiency (28%) and slightly water content (2%) in inoculated S. ramosissima. Finally, our results demonstrated that S. ramosissima was able to accumulate great concentrations of heavy metals, mostly at root level, up to 200 mg Kg–1 arsenic, 0.50 mg Kg–1 cadmium, 400 mg Kg–1 copper, 25 mg Kg–1 nickel, 300 mg Kg–1 lead, and 300 mg Kg–1 zinc. Bioaugmentation incremented S. ramosissima heavy metal phytoremediation potential due to plant biomass increment, which enabled a greater accumulation capacity. Thus, our results suggest the potential use of heavy metal resistant PGPB to ameliorate the capacity of S. ramosissima as candidate for phytoremediation of salty polluted ecosystems.